Verbal instruction does not change myoelectric activity during seated row exercise in trained and untrained men - Rafael A. Fujita; Pedro U. De Marchi; Nilson R. S. Silva; Matheus M. Gomes (Universidade Estadual Paulista (UNESP), 2019)
Abstract Aims: This study aimed to analyze the effect of verbal instruction on myoelectric activity (EMG) of the elbow flexors and shoulder extensors muscles during seated row exercise at 70%1RM, in trained and untrained individuals. Methods: The study sample comprised of seven males (21 ± 1.9 years) who had not practiced resistance training for at least one year (untrained group), and eight males (23 ± 2.6 years) who had regularly practice strength training for 2.4 ± 0.7 years (trained group). All individuals performed the seated row exercise with 70%1RM in conditions with and without verbal instruction. The EMG of the latissimus dorsi, teres major, posterior deltoid, triceps brachii long head and biceps brachii were measured. Results: There was no effect of verbal instruction on EMG at any muscle analyzed, for both groups. There was a difference between groups only for the teres major and triceps brachii (p < 0.05). Untrained individuals had greater myoelectric activity in teres major and triceps brachii long head muscles compared to the trained group during the exercise.